European undergraduate curriculum in geriatric medicine developed using an international modified Delphi technique - Masud, Tahir; Blundell, Adrian; Gordon, Adam Lee; Mulpeter, Ken; Roller, Regina; Singler, Katrin; Goeldlin, Adrian; Stuck, Andreas (Age and Ageing, 2014)
the rise in the number of older, frail adults necessitates that future doctors are adequately trained in the skills of geriatric medicine. Few countries have dedicated curricula in geriatric medicine at the undergraduate level. The aim of this project was to develop a consensus among geriatricians on a curriculum with the minimal requirements that a medical student should achieve by the end of medical school.a modified Delphi process was used. First, educational experts and geriatricians proposed a set of learning objectives based on a literature review. Second, three Delphi rounds involving a panel with 49 experts representing 29 countries affiliated to the European Union of Medical Specialists (UEMS) was used to gain consensus for a final curriculum.the number of disagreements following Delphi Rounds 1 and 2 were 81 and 53, respectively. Complete agreement was reached following the third round. The final curriculum consisted of detailed objectives grouped under 10 overarching learning outcomes.a consensus on the minimum requirements of geriatric learning objectives for medical students has been agreed by European geriatricians. Major efforts will be needed to implement these requirements, given the large variation in the quality of geriatric teaching in medical schools. This curriculum is a first step to help improve teaching of geriatrics in medical schools, and will also serve as a basis for advancing postgraduate training in geriatrics across Europe.
EVALuna2:10401